Insights Into Translatomics in the Nervous System - Zhang, Shuxia; Chen, Yeru; Wang, Yongjie; Zhang, Piao; Chen, Gang; Zhou, Youfa (Frontiers in Genetics, 2020)
Most neurological disorders are caused by abnormal gene translation. Generally, dysregulation of elements involved in the translational process disrupts homeostasis in neurons and neuroglia. Better understanding of how gene translation process requires detailed analysis of transcriptomic and proteomic profile data. However, a lack of strictly direct correlation between mRNA and protein levels limits translational investigation by combining transcriptomic and proteomic profiling. The much better correlation between proteins and translating mRNAs than total mRNAs in abundance and insufficiently sensitive proteomics approach promote the requirement of advances in translatomics technology. Translatomics which capture and sequence the mRNAs associated with ribosomes has been effective in identifying translational changes by genetics or projections, ribosome stalling, local translation and transcript isoforms in the nervous system. Here, we place emphasis on the main three translatomics methods currently used to profile mRNAs attached to ribosome-nascent chain complex (RNC-mRNA). Their most prominent application prospects of each method are outlined. The data reviewed here expands our understanding on the contributions of aberrant translation to neurological disease development.